Company analysis Pos Malaysia Berhad / Nur Liyana Kamaruddin ... [et al.] - Kamaruddin, Nur Liyana; Abdul Rahim, Rosilah; Kamaruddin, Irrawanita; Sidek, Muhammad Amir Akram (2020)
We gladly present our case studies on delivery services provided by Pos Malaysia. Where, the delivery service provided is not as promised. Based on our observations and research, most customers complain about delivery via Pos Malaysia are very slow and sometimes the courier were not received. We prepared this case study to find the causes and ensure the best solutions to improve process of courier. Pos Malaysia Berhad is the first postal services company in Malaysia. Where, they provide a wide range of services such as postal service, courier, financial services, payment services and so on. Pos Malaysia also has large coverage service around Malaysia where this can make their customer easy to deal. We assume that this is one of why customer still demand on Pos Malaysia even they have a lot of complaints. Pos Malaysia vision is to "Connecting Malaysia and Beyond - For Today and Tomorrow". It shows that Pos Malaysia must act fast for their services in order to achieve their vision. Based on that, we have done some research and observation to find the causes and present recommendation to Pos Malaysia for their service improvement. We use Business Model Canvas (BMC) to determine on how the company create, delivers and capture value of their services. We assume that Pos Malaysia has variety of service that can make customer or business people choose. This is due to wide coverage and cheaper services. We also use SWOT analysis to compare the strength and weakness between Pos Malaysia and their competitor. We assume that Pos Malaysia have opportunity to be more competitiveness if they can make improvement. Based on our further discussion, we recommend that Pos Malaysia need to improve in terms of employee skills and knowledge. Where, we assume that their employee have less experience on how to handle the customer, especially employee in customer services. Furthermore, Pos Malaysia also need to upgrade their apps system to be more accurate and improve their shipment process. This is to ensure customer product will sent at the right place and at the right time. For example, maybe Pos Malaysia can implement digital rating by customer to their in front liner employee, so that the customer can get the fast response.